Exploiting the potential of Cyanidiales as a valuable resource for biotechnological applications. Issue 1 (31st December 2022) - Lang, Imke; Bashir, Samirul; Lorenz, Maike; Rader, Stephen; Weber, Gert
ABSTRACT: The biotechnological uses of algae and cyanobacteria have been widely discussed in the context of climate change and consequent efforts to circularize economies, minimize carbon release and reuse waste streams. Their great potential in bioproduction and bioremediation has barely been exploited, particularly for the well-characterized red algae Galdieria sulphuraria and Cyanidioschyzon merolae . These and other Cyanidiales are excellent candidates for biotechnological enhancement and metabolic engineering for a broad spectrum of applications including the production of biofuels and thermostable colourants. In particular, extremophily, such as growth at thermophilic temperatures – up to 60°C – and at low pH and high salinity, make these algae unusually resistant to contamination and pathogens, and therefore potentially more commercially viable. We review existing applications of the Cyanidiales, as well as their available molecular tools. Their varied nutritional demands, from the broad heterotrophy of G. sulphuraria to strongly autotrophic C. merolae, along with their ability to grow to high densities, confer great potential as expression hosts. We also discuss the deficiencies that must be overcome to unlock further applications and ultimately to embed thermophilic red algae into a framework of circular and sustainable economic activity relying on bio-based sources. GRAPHICAL ABSTRACT: uf0001